Prevalence & antibiotic susceptibility patterns Of pathogens obtained from the lower respiratory tract Of patients from NIDCH Dhaka-Bangladesh - Gordon, Kisuule (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.